Thinking about going to the dentist: a Contemplation Ladder to assess dentally-avoidant individuals' readiness to go to a dentist - Hillstead M Blake; Johnson Elissa K; Heima Masahiro; Skaret Erik; Coolidge Trilby; Farjo Nadia; Asmyhr Oyvind; Weinstein Philip (BMC, 2011)
Abstract Background The Transtheoretical Model suggests that individuals vary according to their readiness to change behavior. Previous work in smoking cessation and other health areas suggests that interventions are more successful when they are tailored to an individual's stage of change with regards to the specific behavior. We report on the performance of a single-item measure ("Ladder") to assess the readiness to change dental-avoidant behavior. Methods An existing Contemplation Ladder for assessing stage of change in smoking cessation was modified to assess readiness to go to a dentist. The resulting Ladder was administered to samples of English-speaking adolescents (USA), Spanish-speaking adults (USA), and Norwegian military recruits (Norway) in order to assess construct validity. The Ladder was also administered to a sample of English-speaking avoidant adolescents and young adults who were enrolled in an intervention study (USA) in order to assess criterion validity. All participants also had dental examinations, and completed other questionnaires. Correlations, chi square, t tests and one-way ANOVAs were used to assess relationships between variables. Results In two samples, participants who do not go to the dentist had significantly more teeth with caries; in a third sample, participants who do not go to the dentist had significantly worse caries. Ladder scores were not significantly related to age, gender, caries, or dental fear. However, Ladder scores were significantly related to statements of intention to visit a dentist in the future and the importance of oral health. In a preliminary finding, Ladder scores at baseline also predicted whether or not the participants decided to go to a dentist in the intervention sample. Conclusions The data provide support for the convergent and divergent construct validity of the Ladder, and preliminary support for its criterion validity. The lack of relationship between dental fear and Ladder scores suggests that avoidant individuals may be helped to decide to go to a dentist using interventions which do not explicitly target their fear.